The Development of Jateng Gayeng Monopoly Media: Learn Unit Conversion by Loving Culture - Permatasari, Bella Ayu; Prihatnani, Erlina (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
Math exercises need to be presented in an appealing and pleasing approach. This study aims to promote learning media in the form of a monopoly game as a medium to learn unit conversion while getting to know Central Java cultures. This Research and Development study utilized the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The data collection methods that were used were documentation, tests, and questionnaires. The Jateng Gayeng Monopoly Media had been validated by lecturers and mathematics teachers and declared legally valid with a percentage of 88.8% (excellent), and efficient with a rate of 87.4%. This learning media has also been tested on fifth-grade students of SDN Watuagung 02 Semarang Regency. Moreover, based on the result of the Wilcoxon test at the significant level Î± = 0.05, it can be concluded that the Jateng Gayeng Monopoly Media effectively enhances students' learning outcomes. This result is expected to inspire the growth of learning media, which elevates Indonesia's local cultures so that Indonesian children will be more proud and love their cultures.Latihan soal perlu disajikan secara menarik agar tidak membosankan. Penelitian ini bertujuan untuk mengembangkan media pembelajaran monopoli yang dapat digunakan sebagai sarana latihan soal konversi satuan sambil mengenal budaya Jawa Tengah. Penelitian Research and Development ini menggunakan model pengembangan ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Metode pengumpulan data yang digunakan ialah dokumentasi, tes, dan angket. Media Monopoli Jateng Gayeng divalidasi oleh dosen dan guru matematika dan dinyatakan valid dengan persentase 88,8% (sangat baik) dan sangat praktis dengan persentase 87,4%. Media ini telah diujicobakan terhadap siswa kelas V SDN Watuagung 02 Kabupaten Semarang dan berdasarkan hasil uji Wilcoxon pada taraf signifikan Â 0.05 disimpulkan bahwa monopoli Jateng Gayeng efektif untuk meningkatkan hasil belajar siswa. Hasil ini diharapkan dapat menginspirasi munculnya media latihan soal yang mengaitkan dengan budaya lokal daerah-daerah di Indonesia agar anak Indonesia makin bangga dan cinta akan budaya yang dimiliki.